2023
DOI: 10.3389/fsufs.2023.1222760
|View full text |Cite
|
Sign up to set email alerts
|

Food product quality, environmental and personal characteristics affecting consumer perception toward food

Sampurna Rai,
Phu Pwint Wai,
Pankaj Koirala
et al.

Abstract: Food industries are developing new processing technologies, resulting in the emergence of new product categories, including ready-to-eat meals, functional foods and beverages, and plant-based foods, etc. Rapid globalization, changes in lifestyle, consumer awareness, and perception toward food drive further technical advancements. However, consumer perception remains the prime factor for food marketing and technological development. Consumer perception is a trifecta of sensory properties, personal and environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 102 publications
0
0
0
Order By: Relevance
“…Sensory properties of foods are principally the outcome of the interaction of food characteristics/quality (such as physical structure and chemical/nutritional properties) and the consumer's characteristics (gender, age, attitude, and physiological/psychological state) and its environment (family, cultural traditions, and education) [1][2][3][4][5]40]. Among sensory and personal factors, health conditions significantly influence consumer choice [3,40]. It has been reported that the decline in olfactory and gustatory function greatly affects food sensory perception and eating behavior [6][7][8][9][10][11][13][14][15][16]].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory properties of foods are principally the outcome of the interaction of food characteristics/quality (such as physical structure and chemical/nutritional properties) and the consumer's characteristics (gender, age, attitude, and physiological/psychological state) and its environment (family, cultural traditions, and education) [1][2][3][4][5]40]. Among sensory and personal factors, health conditions significantly influence consumer choice [3,40]. It has been reported that the decline in olfactory and gustatory function greatly affects food sensory perception and eating behavior [6][7][8][9][10][11][13][14][15][16]].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to dried shrimp, RTE shrimp has a higher moisture content and good taste. The sensory properties of RTE shrimp, which include many factors such as color, flavor, and texture, are of great importance to consumers [5]. Due to the action of astaxanthin, boiled shrimp has a bright pink color.…”
Section: Introductionmentioning
confidence: 99%
“…Commodity flavor and texture significantly influence consumer choice (Byrne, 2020; Rai et al, 2023), with these sensory properties—such as sourness, sweetness, bitterness, saltiness, and freshness—primarily detected by the taste buds on the tongue. Established methods are available to assess these flavors (Fan et al, 2023; Song et al, 2023; Yang et al, 2022; Yu et al, 2023; Zheng et al, 2023), but other properties such as astringency and smoothness are challenging to characterize with conventional techniques.…”
Section: Introductionmentioning
confidence: 99%